One step closer to preschool-aged children's self-regulation: conceptualization and investigation of its correlates during everyday life - Ludwig, Katja (2018)
The ability to self-regulate one's own attention, behavior, and emotions is essential for healthy trajectories. The present thesis complements previous research by providing first evidence that preschoolers' self-regulation should be considered as a multi-faceted construct, with intra-individual variability (i.e., daily fluctuations) in addition to inter-individual differences and divergent relations. There is first evidence that daily variability in preschoolers' succesful self-regulation seems to be directly explained by their daily positive affective states and indirectly by habitual physical activity through positive affect, indicating that these child-level variables may constitute promising psychological resources for children's successful self-regulation, occurring in their everyday life. In addition, different parenting behaviors and facets of the home context seem to be differently related according to preschoolers' self-regulation facet. By investigating preschoolers' multi-faceted self-regulation skills and their correlates during everyday lives, the present thesis gets one step closer and contributes to the mosaic of the rising field of self-regulation research.
Keywords: Hochschulschrift